DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON COMPUTER TO IMPROVE STUDENT LEARNING MOTIVATION - Kartika Bunga Nadhya Noor; Mimin Nur Aisyah (Universitas Negeri Yogyakarta, 2018)
This research is aimed at developing interactive learning media for class X student of Accounting Major at SMK Muhammadiyah 1 Yogyakarta with basic competency materials Making Adjustment Journal Entries and also examines the feasibility of interactive learning media as well as investigate the improvement of student learning motivation after using the media. This research used Research and Development (R D) models and adapted ADDIE development model, which include 5 phases, namely: Analysis, Design, Development, Implementation, and Evaluation. The measurement of students learning motivation used questionnaire filled by 33 students of class X AK 1 as treatment group and 33 students of class X AK 2 as control group. The research results show that interactive learning media in Basic Accounting Subject declared as Strongly Feasible category with average scores of 4.5 by material expert, 4.47 by media expert, 4.35 by accounting teacher, and 4.29 by students. Based on student learning motivation analysis, the treatment group obtain an increase of 6% from 73% to 79% and control group obtain an increase of 2% from 74% to 76%. Keywords: Interactive Learning Media, Student Learning Motivation, ADDIE, Basic Accounting, Adjustment Journal Entries